Bitcoin and Beyond : Cryptocurrencies, Blockchains, and Global Governance - Malcolm Campbell-Verduyn (Routledge, 2017)
Since the launch of Bitcoin in 2009 several hundred different ‘cryptocurrencies'have been developed and become accepted for a wide variety of transactions in leading online commercial marketplaces and the ‘sharing economy', as well as by more traditional retailers, manufacturers, and even by charities and political parties. Bitcoin and its competitors have also garnered attention for their wildly fluctuating values as well as implication in international money laundering, Ponzi schemes and online trade in illicit goods and services across borders. These and other controversies surrounding cryptocurrencies have induced varying governance responses by central banks, government ministries, international organizations, and industry regulators worldwide. Besides formal attempts to ban Bitcoin, there have been multifaceted efforts to incorporate elements of blockchains, the peer-to-peer technology underlying cryptocurrencies, in the wider exchange, recording, and broadcasting of digital transactions. Blockchains are being mobilized to support and extend an array of governance activities. The novelty and breadth of growing blockchain-based activities have fuelled both utopian promises and dystopian fears regarding applications of the emergent technology to Bitcoin and beyond. This volume brings scholars of anthropology, economics, Science and Technology Studies, and sociology together with GPE scholars in assessing the actual implications posed by Bitcoin and blockchains for contemporary global governance. Its interdisciplinary contributions provide academics, policymakers, industry practitioners and the general public with more nuanced understandings of technological change in the changing character of governance within and across the borders of nation-states.